Scattering singularity in topological dielectric photonic crystals - Xiong, Langlang (2024)
The exploration of topology in natural materials and metamaterials has garnered significant attention. Notably, the one-dimensional (1D) and two-dimensional (2D) Su-Schrieffer-Heeger (SSH) models, assessed through tight-binding approximations, have been extensively investigated in both quantum and classical systems, encompassing general and higher-order topology. Despite these advancements, a comprehensive examination of these models from the perspective of wave physics, particularly the scattering view, remains underexplored. In this study, we systematically unveil the origin of the 1D and 2D Zak phases stemming from the zero-reflection point, termed the scattering singularity in momentum space. Employing an expanded plane wave expansion, we accurately compute the reflective spectrum of an infinite 2D photonic crystal (2D-PhC). Analyzing the reflective spectrum reveals the presence of a zero-reflection line in the 2D-PhC, considered the topological origin of the nontrivial Zak phase. Two distinct models, representing omnidirectional nontrivial cases and directional nontrivial cases, are employed to substantiate these findings. Our work introduces a perspective for characterizing the nature of nontrivial topological phases. The identification of the zero-reflection line not only enhances our understanding of the underlying physics but also provides valuable insights for the design of innovative devices.